Evaluation of the neuroprotective efficacy of the gramine derivative ITH12657 against NMDA-induced excitotoxicity in the rat retina - Di Pierdomenico, Johnny; Gallego-Ortega, Alejandro; Norte-Muñoz, María; Vidal-Villegas, Beatriz; Bravo, Isaac; Boluda-Ruiz, María; Bernal-Garro, Jose Manuel; Fernandez-Bueno, Iván; Pastor-Jimeno, Jose Carlos; Villegas-Pérez, María Paz; Avilés-Trigueros, Marcelino; de los Ríos, Cristobal; et al. (Frontiers in Neuroanatomy, 2024)
Purpose The aim of this study was to investigate, the neuroprotective effects of a new Gramine derivative named: ITH12657, in a model of retinal excitotoxicity induced by intravitreal injection of NMDA. Methods Adult Sprague Dawley rats received an intravitreal injection of 100 mM NMDA in their left eye and were treated daily with subcutaneous injections of ITH12657 or vehicle. The best dose–response, therapeutic window study, and optimal treatment duration of ITH12657 were studied. Based on the best survival of Brn3a + RGCs obtained from the above-mentioned studies, the protective effects of ITH12657 were studied in vivo (retinal thickness and full-field Electroretinography), and ex vivo by quantifying the surviving population of Brn3a + RGCs, αRGCs and their subtypes α-ONsRGCs, α-ONtRGCs, and α-OFFRGCs. Results Administration of 10 mg/kg ITH12657, starting 12 h before NMDA injection and dispensed for 3 days, resulted in the best significant protection of Brn3a + RGCs against NMDA-induced excitotoxicity. In vivo, ITH12657-treated rats showed significant preservation of retinal thickness and functional protection against NMDA-induced retinal excitotoxicity. Ex vivo results showed that ITH12657 afforded a significant protection against NMDA-induced excitotoxicity for the populations of Brn3a + RGC, αRGC, and αONs-RGC, but not for the population of αOFF-RGC, while the population of α-ONtRGC was fully resistant to NMDA-induced excitotoxicity. Conclusion Subcutaneous administration of ITH12657 at 10 mg/kg, initiated 12 h before NMDA-induced retinal injury and continued for 3 days, resulted in the best protection of Brn3a + RGCs, αRGC, and αONs-RGC against excitotoxicity-induced RGC death. The population of αOFF-RGCs was extremely sensitive while α-ONtRGCs were fully resistant to NMDA-induced excitotoxicity.